2018
DOI: 10.18203/2320-6012.ijrms20180622
|View full text |Cite
|
Sign up to set email alerts
|

Profile of neonatal dermatoses in a tertiary care teaching hospital of Haryana

Abstract: Background: To assess the incidence and profile of neonatal dermatoses in a tertiary care hospital of Haryana and study its association with various perinatal risk factors.Methods: All inborn neonates (<28 days of life) including those seen in the outpatient department on follow up between November 2016 to April 2017 formed the baseline population and babies with skin lesions were included in the study. A detailed perinatal history and newborn examination of the baby was done by a pediatrician and all relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Skin changes are affected by hereditary,race,gestational age and maternal health in addition to other external factors such as hygiene, socioeconomic status, customs, mode of delivery etc 8 . Neonatal dermatosis are a very common cause of parental anxiety and concern pressing the need for appropriate diagnosis and counseling of parents.This avoids unnecessary diagnostic and therapeutic interventions 9 . A number of studies have been reported on neonatal dermatosis but none from this region of Bangladesh.…”
Section: Neonatal Dermatosis Are Classified As Followsmentioning
confidence: 99%
“…Skin changes are affected by hereditary,race,gestational age and maternal health in addition to other external factors such as hygiene, socioeconomic status, customs, mode of delivery etc 8 . Neonatal dermatosis are a very common cause of parental anxiety and concern pressing the need for appropriate diagnosis and counseling of parents.This avoids unnecessary diagnostic and therapeutic interventions 9 . A number of studies have been reported on neonatal dermatosis but none from this region of Bangladesh.…”
Section: Neonatal Dermatosis Are Classified As Followsmentioning
confidence: 99%